An Assessment of the Karkheh’s Multi-Reservoir Systems’ Operation Coordinating Impacts on the long-Term Water Supply at Different Stages of Basin Development - A. A; A. K (مهندسی منابع آب, 2013)
Watershed system configuration and conditions change as newer water supply, irrigation, industry and municipal development projects are constructed. In such a new condition, applying the current operating rules for reservoirs, aside from not being optimum, will produce different economic and social costs, too. Therefore, it is necessary to coordinate the operation in the new condition and update reservoirs operating rules. Coordinating the hydro-system operation and updating the reservoirs, operation rules at different stages of the basin development are studied in this research. Therefore, a long-term optimization model is developed, which takes into account the upstream operation impacts on the downstream performance, and coordinates operation of different hydro-system components in a manner to maximize satisfaction of different stakeholders’ targets as much as possible. Application of the model to the Karkheh’s hydro-system analysis at different development stages for an assessment of coordination and updating of operation impacts shows that after construction of the Karkheh, Saymareh and Sazbon Dams, 60% of water demand targets will not be met in comparison with the updated rule curves application if the primary rule curves of dams that are determined for each dam are used individually in practice. Besides, non- coordination of the Karkheh’s hydro-system operation and updating reservoirs operation rules will reduce water supply reliability by 50% in a 20 year planning horizon in comparison with a coordinated and updated operation of the Karkheh’s hydro-system.